INTERFERENSI BUDAYA DALAM PILIHAN LEKSIKON SISWA KELAS BAHASA INDONESIA BAGI PENUTUR ASING DI BANDUNG INDEPENDENT SCHOOL - Hafshah Nur'aini, Zakia; Sundusiah, Suci; Whilky Rizkyanfi, Mochamad (JURNAL KONFIKS, 2026)
This study aims to describe the forms of cultural interference in the lexical choices of BIPA students at Bandung Independent School who come from Korea, America, and Germany. This study uses a descriptive qualitative approach with a communication ethnography framework to examine language use practices in real and contextual learning situations. Research data were collected through participatory observation conducted during the learning process and documentation in the form of class interaction transcripts and field notes recording communication events between teachers and students as well as among students. The results show that cultural interference consistently appears in various communication events, particularly when students respond to teacher instructions, express opinions, engage in group discussions, and interact informally in class. Students from Korea tended to use vocabulary that reflected layered politeness and caution in speech, students from America displayed a more direct, expressive, and egalitarian style of language, while students from Germany used concise, systematic, and rational vocabulary. These differences indicate that students' lexical choices are not solely influenced by their linguistic competence in Indonesian, but also by the cultural norms of their countries of origin, which shape their communication habits and strategies. These findings emphasize the importance of integrating cultural and pragmatic aspects into BIPA learning so that learners are able to use Indonesian appropriately, both linguistically and socio-communicatively.